2013
DOI: 10.2519/jospt.2013.4679
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Talocrural Joint Laxity: Diagnostic Accuracy of the Anterior Drawer Test of the Ankle

Abstract: Study Design Prospective, blinded, diagnostic-accuracy study. Objectives To investigate the diagnostic accuracy of the ankle anterior drawer test (ADT) to detect anterior talocrural joint laxity in adults with a history of lateral ankle sprain. Background The ADT is used to manually detect anterior talocrural joint laxity following lateral ankle sprain injury; however, the diagnostic accuracy of this test has not been established. Methods Sixty-six subjects with a history of lateral ankle sprain were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 42 publications
2
72
0
Order By: Relevance
“…Previous studies have attempted to identify alterations in mechanical laxity between those with and without CAI, with some indicating increased laxity in CAI participants compared with healthy controls (Cordova et al, 2010;Croy et al, 2012) and increased ligament lengthening in copers compared with controls (Croy et al, 2012). A previous study using a population similar to this study reported low diagnostic accuracy for the anterior drawer test (Croy et al, 2013). The values were relatively similar to ours even with this different manual test (Croy et al, 2013).…”
Section: Specificity Sensitivity Likelihood Ratios and Diagnosticsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous studies have attempted to identify alterations in mechanical laxity between those with and without CAI, with some indicating increased laxity in CAI participants compared with healthy controls (Cordova et al, 2010;Croy et al, 2012) and increased ligament lengthening in copers compared with controls (Croy et al, 2012). A previous study using a population similar to this study reported low diagnostic accuracy for the anterior drawer test (Croy et al, 2013). The values were relatively similar to ours even with this different manual test (Croy et al, 2013).…”
Section: Specificity Sensitivity Likelihood Ratios and Diagnosticsupporting
confidence: 89%
“…A previous study using a population similar to this study reported low diagnostic accuracy for the anterior drawer test (Croy et al, 2013). The values were relatively similar to ours even with this different manual test (Croy et al, 2013). A previous study using talar tilt indicated sensitivity 0.5, specificity 0.88, +LR 4 and -LR 0.57 (Hertel et al, 1999;Schwieterman et al, 2013).…”
Section: Specificity Sensitivity Likelihood Ratios and Diagnosticsupporting
confidence: 86%
See 2 more Smart Citations
“…The talar tilt test also helps determine CFL competence. The sensitivity of these tests is variable and ranges from 74 to 96% [33][34][35][36][37]. Regardless, performing a manual physical exam is an important part of assessing a patient presenting with ankle instability.…”
Section: History and Physical Examinationmentioning
confidence: 99%